2014
DOI: 10.3171/2014.5.focus1483
|View full text |Cite
|
Sign up to set email alerts
|

Use of computed tomography for assessing bone mineral density

Abstract: Assessing local bone quality on CT scans with Hounsfield unit (HU) quantification is being used with increasing frequency. Correlations between HU and bone mineral density have been established, and normative data have been defined throughout the spine. Recent investigations have explored the utility of HU values in assessing fracture risk, implant stability, and spinal fusion success. The information provided by a simple HU measurement can alert the treating physician to decreased bone quality, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
141
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(149 citation statements)
references
References 35 publications
3
141
0
5
Order By: Relevance
“…[26] Furthermore, the related research had reported that the average HU value of spine depending on different age groups decreased as the patients’ age increased and the differences in HU values from L1 to 4th Lumbar were significant among different age groups. [27, 35, 36] Therefore, our finding suggests that each 3D printing technique has its own special advantage in terms of the HU value that depends on the patient’s age and it also demonstrated that careful selection of the 3D printing technique and printing materials is required since even when the same material, which is known to have a similar density to the human spine, was applied for 3D printing, the calculated HU values from two different 3D printed spine phantom sets were different.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Furthermore, the related research had reported that the average HU value of spine depending on different age groups decreased as the patients’ age increased and the differences in HU values from L1 to 4th Lumbar were significant among different age groups. [27, 35, 36] Therefore, our finding suggests that each 3D printing technique has its own special advantage in terms of the HU value that depends on the patient’s age and it also demonstrated that careful selection of the 3D printing technique and printing materials is required since even when the same material, which is known to have a similar density to the human spine, was applied for 3D printing, the calculated HU values from two different 3D printed spine phantom sets were different.…”
Section: Discussionmentioning
confidence: 99%
“…First, we used CTderived HU to estimate the degree of BMD reduction. Although the gold standard for measuring BMD is the DEXA scan, several studies demonstrate the utility of diagnostic CT scan in providing reliable estimates for regional bone strength and BMD [10][11][12][13]. Secondly, this study is a retrospective review of patients treated at a single institution.…”
Section: Discussionmentioning
confidence: 99%
“…Although dual-energy X-ray absorptiometry (DEXA) serves as the gold standard for BMD quantification, several studies have determined that the BMD provided by DEXA has a strong correlation with CT-derived Hounsfield units (HU), can provide reliable estimates for regional bone strength and BMD, and accurately rule out osteoporosis with better than 90% sensitivity [10][11][12][13]. Since diagnostic CT scans are ordered routinely to monitor response to treatments, we can utilize CT-derived HU to monitor BMD in patients, while avoiding the need for additional DEXA imaging and improving resource utilization.…”
mentioning
confidence: 99%
“…Одним из наиболее важных факторов, вли-яющих на сохранение стабильности имплантов после декомпрессивно-стабилизирующих опера-тивных вмешательствах, является качество кост-ной ткани, что было неоднократно подтвержде-но результатами исследований [6,13,14]. Тем не менее способы оценки костной плотности в опубликованных работах отличаются: чаще всего с ýтой целью применялась денситометрия, коли-чественная компьютерная томография, и радио-денсивность костной ткани, определенная при КТ, использовались реже [6,7,14].…”
Section: результаты и обсуждениеunclassified